1988
DOI: 10.2527/jas1988.66123040x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods of Predicting Breeding Values of Swine

Abstract: Best linear unbiased predictions (BLUP) using information from all known relatives; selection index using phenotype, full-sib average and half-sib average; and phenotypie deviation from contemporary group average were compared as methods of predicting breeding values for days to 100 kg and backfat. Swine records (n = 203,869) from five Hampshire, one Duroc and six Yorkshire herds were obtained from the Nebraska SPF Swine Accrediting Agency. Heritability values used to compute BLUP or index were either estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
4

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
3
6
0
4
Order By: Relevance
“…A metodologia de modelos mistos para avaliação genética de suínos tem sido empregada e recomendada por vários pesquisadores em melhoramento animal (SORENSEN e KENNEDY, 1986;KEELE et al, 1988;LOPES, 1994a;MARTINS, 1995;e TORRES JR., 1996) e indicada por fornecer predições não-viesadas de efeitos genéticos, efeitos comuns ou permanentes de ambiente e de grupo de animais, efeitos maternos e de endogamia, e efeitos de seleção, entre outros.…”
Section: Pires Et Al Modelos Lineares Mistos E Dados Desbalanceadosunclassified
“…A metodologia de modelos mistos para avaliação genética de suínos tem sido empregada e recomendada por vários pesquisadores em melhoramento animal (SORENSEN e KENNEDY, 1986;KEELE et al, 1988;LOPES, 1994a;MARTINS, 1995;e TORRES JR., 1996) e indicada por fornecer predições não-viesadas de efeitos genéticos, efeitos comuns ou permanentes de ambiente e de grupo de animais, efeitos maternos e de endogamia, e efeitos de seleção, entre outros.…”
Section: Pires Et Al Modelos Lineares Mistos E Dados Desbalanceadosunclassified
“…In pigs, numerous studies have been conducted to evaluate the advantage of using BLUP instead of standard selection indexes in a variety of situations (Belonsky and Kennedy, 1988;Keele et al, 1988;Sorensen, 1988; Wray, 1989;Long et al, 1990; De Vries et al, 1990;Roehe et al, 1990). National genetic evaluation programmes based on the BLUP-IAM technique have been implemented in several countries since 1985 (Hudson and Kennedy, 1985;Van Hofstraeten and Vandepitte, 1988;Harris et al, 1989; Sorensen and Vernessen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…But, several recent studies (Belonsky and Kennedy, 1988;Keele et al, 1988) have indicated that even with high heritability, BLUP results in greater accuracy of evaluation than selection on phenotype or index. Keele et al (1988) also concluded that BLUP is robust to errors in estimated heritability.…”
Section: Ties Across Testsmentioning
confidence: 99%
“…In recent years, results of mixedmodel analyses of swine data have been reported with increasing frequency Mabry et al, 1987;Keele et al, 1988). Most research on mixed-model methodology has been conducted using design structures commonly found in cattle data.…”
Section: Introductionmentioning
confidence: 99%